2022
DOI: 10.1111/jcpe.13690
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gingivitis is associated with reduction of systemic inflammation and improvement of oral health‐related quality of life: A randomized clinical trial

Abstract: Aim To compare the level of inflammatory markers, oral health‐related quality of life (OHRQoL), and gingival parameters 1 month after introduction of electric toothbrush and intensive oral hygiene manoeuvre adaptation (OHI) versus routine habits (no‐OHI) in patients affected by generalized gingivitis. Materials and Methods One hundred forty subjects with generalized gingivitis were randomized to receive either OHI or no‐OHI. Full‐mouth plaque/bleeding scores (FMPS/FMBS), serum high‐sensitivity C‐reactive prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Through the mechanical elimination of the biofilm as a component of periodontal therapy, the difficulty was diminished, resulting in a decrease in the production of these cytokines. A recent study found the resolution of gingivitis is associated with significant reductions in both gingival inflammation and plaque levels, as well as systemic inflammatory markers [25]. In a comparison between HA/ H2O2 with CHX mouthwashes, the present findings revealed that CHX mouthwash had the highest effect in lowering IL-1B and IL-6 levels when compared to HA/ H2O2 mouthwash.…”
Section: Groupssupporting
confidence: 54%
“…Through the mechanical elimination of the biofilm as a component of periodontal therapy, the difficulty was diminished, resulting in a decrease in the production of these cytokines. A recent study found the resolution of gingivitis is associated with significant reductions in both gingival inflammation and plaque levels, as well as systemic inflammatory markers [25]. In a comparison between HA/ H2O2 with CHX mouthwashes, the present findings revealed that CHX mouthwash had the highest effect in lowering IL-1B and IL-6 levels when compared to HA/ H2O2 mouthwash.…”
Section: Groupssupporting
confidence: 54%
“…Several studies have suggested a strong link between noncommunicable diseases and oral health, with demonstrated associations with oral diseases for various conditions including cancer, diabetes, cardiovascular diseases, depression, neurodegenerative conditions, rheumatic diseases, inflammatory bowel disease, gastric helicobacter pylori, obesity, and asthma [ 18 ]. The connection between oral health and these diseases is largely attributed to inflammation, although there are two other pathways that may explain the association [ 19 , 20 , 21 ]. Firstly, some systemic diseases have direct links to negative impacts on oral health and oral health-related quality of life (OHRQoL), such as Crohn’s disease [ 22 , 23 ], Beçhet’s disease [ 24 , 25 , 26 ], scleroderma [ 27 , 28 ], oral cancer [ 29 , 30 , 31 , 32 ], head and neck cancer [ 33 ], and Sjögren’s syndrome [ 34 , 35 , 36 , 37 ].…”
Section: Diseases and Oral Healthmentioning
confidence: 99%
“…Several studies have suggested a strong link between noncommunicable diseases and oral health, with demonstrated associations with oral diseases for various conditions including cancer, diabetes, cardiovascular diseases, depression, neurodegenerative conditions, rheumatic diseases, inflammatory bowel disease, gastric helicobacter pylori, obesity, and asthma [18]. The connection between oral health and these diseases is largely attributed to inflammation, although there are two other pathways that may explain the association [19][20][21]. Firstly, some systemic diseases have direct links to negative impacts on oral health and oral health-related quality of life (OHRQoL), such as Crohn's disease, Beçhet's disease, oral cancer, Sjögren's syndrome, and scleroderma [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Diseases and Oral Healthmentioning
confidence: 99%